Role of Biomarkers for Detection, Diagnosis and Targeted Therapy of Gynecological Cancers - Gupta, Seema (Journal of Neonatal Surgery, 2025)
Cancer is the uncontrollable abnormal division of cell growth, caused due to the varied reasons. Cancer can be expressed in any part of the body, and it is one of the death-causing diseases. Human reproductive organs are commonly damaged by cancer. In particular, the women reproductive system is affected by various cancers including ovarian, cervical, endometrial, vaginal, fallopian tube, and vulvar cancers. Identifying these cancers at earlier stages prevents the damage to the organs. Different biomarkers and aptamers have been generated against the gynecological cancer, which include, ctDNAs, miRNAs, Antigen 125 (CA125), Folate receptor alpha (FOLR1), Transthyretin (TTR), TIM‑3, VEGF, TGF‑α, TRAIL, MCP‑3, IL‑15, PD‑L2, SCF, CTCs, Exosomes, TEPs, cfRNA, HE4, CA125, VEGF, OCCA (for ovarian cancer), EGFR, FGFR1, K-ras (for endometrial cancer), HPV E-16, HPV E-7, HPV E-6, tyrosine, and kinase (for cervical cancer), which help to identify the cancers in woman reproductive organs. This review provided an overview of current and potential biomarkers for gynecological cancer such as ovarian, endometrial and cervical cancers for early detection, diagnosis and targeted therapy.